The Effect of Reaction Time on the Viscosity and Density of Tetraethyl Orthosilicate from Silica of Rice Husk Ash - Dwi Rasy, Mujiyanti; Hayatun, Nisa; Kholifatu, Rosyidah; Dahlena, Ariyani; Abdullah, .; Wayan Koko, Suryawan; Ani, Purwanti; Wisnu, Prayogo (INTI International University, 2023)
TEOS is a material widely used in various industrial fields. One source of silica (SiO2) is rice husk ash. The purpose of this study was to determine the effect of reaction time on viscosity and density in making TEOS from rice husk silica. Silica resulting from the purification of rice husk ash is used in the TEOS manufacturing process by examining the variation of reaction time. One mole of ethanol (58.4 ml) and 0.25 mole (7 gr) of silica powder were added to a 250 ml round bottom flask, followed by the addition of 1 gr of CuO/Al2O3 catalyst. The mixture was then refluxed for 30, 35, 40, 45, and 50 hours with effective stirring at a temperature of 90°C. The FTIR characterization results show that there are three main functional groups: the -OH, Si-O, and C-O groups in the five TEOS synthesis results. Wave numbers of the –OH functional groups obtained ranged from 3349 cm-1 to 3315 cm-1 ; Si-O functional groups ranged from 813 cm-1 to 606 cm-1 , and C-O functional groups ranged from 1105 cm-1 to 1040 cm-1 . Reaction time has a significant effect on the viscosity and density of the resulting TEOS. The findings indicate that reaction time does not significantly affect the viscosity of TEOS solutions within the investigated time frame. The viscosity values obtained fall within the acceptable range for commercial TEOS, indicating successful production of TEOS solutions with suitable flow characteristics. However, the density values obtained do not meet the requirements for commercial TEOS, highlighting the need for further optimization.